Incidence of gallstones after gastric resection for gastric cancer: a nationwide claims-based study - Seo, Gi Hyeon (Ann Surg Treat Res, 2018)
PURPOSE: Gallstone formation is one of the most common problems after gastrectomy. This retrospective cohort study used the South Korean nationwide claims database to evaluate the incidence and risk factors of gallstone after gastrectomy for gastric cancer. METHODS: All consecutive patients who underwent gastrectomy for gastric cancer in South Korea in 2008–2010 were identified. Incidence of gallstone formation 5 years after gastrectomy in males and females, in various age groups, and after different types of gastrectomy was determined. Multivariate logistic regression analysis served to identify gallstone risk factors. RESULTS: Of the 47,752 patients, 2,506 (5.2%) developed gallstone during the 5-year follow-up period. At 12, 24, 36, and 48 months, the cumulative incidences were 1.2%, 2.2%, 3.3%, and 4.3%, respectively. Males had a higher incidence than females (5.8% vs. 4.1%, P < 0.001). Older patients (60–89 years) had a higher incidence than younger patients (30–59 years) (6.1% vs. 4.3%, P < 0.001). Gallstone was most common after total gastrectomy (6.6%), followed by proximal gastrectomy (5.4%), distal gastrectomy (4.8%), and pylorus-preserving distal gastrectomy (4.0%) (P < 0.001). Multivariate analysis showed that male sex (odds ratio [OR], 1.39), an older age (OR, 1.44), and total gastrectomy (OR, 1.40 vs. distal gastrectomy) were significant independent risk factors for postgastrectomy gallstone. CONCLUSION: The cumulative incidence of gallstone 5 years after gastrectomy for gastric cancer was 5.2%. Male sex, an older age, and total gastrectomy were significant risk factors. More careful monitoring for gallstone may be necessary in patients with such risk factors.